Metale ciężkie w częściach nadziemnych i podziemnych buraków ćwikłowych (beta vulgaris) w otoczeniu zbiornika unieszkodliwiania odpadów poflotacyjnych "Żelazny Most" = Heavy metals in the underground and above-ground parts of the red beet (Beta vulgaris) grown in the direct surroundings of the tailings pond "Żelazny Most" - Kałuża, Andrea; Musztyfaga, Elżbieta; Kozak, Marta; Gałka, Agnieszka; Kabała, Maciej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The work included issues related to the analysis of the current impact of the tailings pond Żelazny Most on the content of heavy metals in red beets grown in home gardens located in the villages of Tarnówek and Komorniki. Analyzes of the contents of Cu, Zn, Pb, Cd show that consumption of the above- and underground parts of rot beet may adversely affect the health of people living there.
Keywords: Żelazny Most; buraki ćwikłowe; Beta vulgaris; metale ciężkie; odpady poflotacyjne; red beet; heavy metals; flotation tailings